The Relationship Between Medication Administration Errors and Professional Attitudes of Pediatric Nurses - Büyük Tural, Esra; Güney, Emine Uzuntarla (My University, 2022)
Objective: This study was carried out to determine the relationship between medication administration errors and professional attitudes of the pediatric nurses. Methods: The study was conducted with 115 pediatric nurses who were working in three hospitals located in a city between 11th January 2020 and 5th January 2021. This was a descriptive and correlational study. A Personal Information Form, Questionnaire for Medication Administration Errors among Pediatric Nurses, Tendency to Medical ErrorTendency Scale (Medication and Transfusion Applications subscale)and the Inventory of Professional Attitude at Occupation were used to collect data. Results: While 34% of the pediatric nursesindicated that they experienced medication administration errors, 52% of them declared that they observed medication administration errors among their colleagues. The nurses also stated the most common medication administration error they experienced (36.5%) and observed (24.8%) was improper dose. It was also determined that the tendency of participants to medication administration errors was low (85.44±5.26) and their professional attitudes were high (140.32±11.33). The tendency of nurses to medication administration errors was determined to differ significantly based on their age, marital status, duration of professional experience, duration of experience in the current clinic and status of satisfaction with the current clinic (p<0.05). It was also determined that the professional attitudes of the participants were significantly correlated with age, education level, professional experience, duration of experience in the current clinic and status of satisfaction with the current clinic(p<0.05). A positive, significant and moderate level of correlation was determined between nurses‟ tendency to make medication administration errors and their professional attitudes (p<0.000; r=0.535). Conclusion: As a result of this study, a significant correlation was found between nurses‟ tendency to medication administration errors and their professional attitudes; and their tendency to make such errors decreased as their professional attitudes increased.
Keywords: Sağlık Politikaları ve Hizmetleri; Sağlık Bilimleri ve Hizmetleri; Hemşirelik